Value of Virtual Touch Quantification Elastography for Assessing Liver Congestion in Patients With Heart Failure - Yoshitani, Takashi; Asakawa, Naoya; Sakakibara, Mamoru; Noguchi, Keiji; Tokuda, Yusuke; Kamiya, Kiwamu; Iwano, Hiroyuki; Yamada, Satoshi; Kudou, Yusuke; Nishida, Mutsumi; Shimizu, Chikara; Amano, Toraji; et al. (Circulation Journal, 2016)
Background:Heart failure (HF) causes organ congestion, which is thought to increase organ stiffness. The virtual touch quantification (VTQ) method can be used to assess liver stiffness in patients with chronic liver diseases. This study aimed to measure liver and kidney stiffness using VTQ and to determine its value for assessing organ congestion in patients with HF.Methods and Results:This study included 10 normal subjects and 38 HF patients (age 52.3±16.7 years, left ventricular ejection fraction 27.0±9.4%, plasma B-type natriuretic peptide [BNP] 1,297.3±1,155.1 pg/ml). We investigated the relationships between clinical characteristics and hemodynamics and liver and kidney stiffness, and assessed the effects of medical treatment on these measurements. Liver stiffness was significantly higher in HF patients (1.17±0.13 m/s vs. 2.03±0.91 m/s, P=0.004) compared with normal subjects, but kidney stiffness was similar in both groups. Central venous pressure (CVP) (P=0.021) and BNP (P=0.025) were independent predictive factors for increased liver stiffness in HF patients. Liver stiffness decreased significantly from 2.37±1.09 to 1.27±0.33 m/s (P<0.001) after treatment. Changes in liver stiffness in HF patients significantly correlated with changes in CVP (R=0.636, P=0.014) and cardiac index (R=−0.557, P=0.039) according to univariate analysis, and with changes in CVP in multivariate analysis.Conclusions:Liver stiffness measured by noninvasive VTQ methods can be used to assess liver congestion and therapeutic effects in patients with HF. (Circ J 2016; 80: 1187–1195)